Educational strategies for the health professions - Miller, George E., 1919-; Fülöp, Tamás (Geneva : World Health Organization, 1974)
Hoe maken we dat de mensen uit de medische sector steeds op de hoogte zijn van de nieuwe technieken en bevindingen?
Walldren, A. W. Curriculum theory and curriculum practice.--McGuire, C. H. and Wezeman, F. H. Simulation in instruction and evaluation in medicine.--Bobula, J. A. Examinations and decision-making.--Perlmutter, S. Dynamics of a working group.--Miller, G. E. Teaching large groups.--McGuire, C. H. Evaluation of teachers and teaching effectiveness.--Foley, R. P. Microteaching for teacher training.--Fülöp, T. The implementation of WHO's training programme for teachers of the health professions.--Miller, G. E. Principle into practice.
Includes bibliographies.
Keywords: Medical teaching personnel -- Training of; Medicine -- Study and teaching